Thermal model validation of an electric-driven smart window through experimental data and evaluation of the impact on a case study. (15th August 2020) - Ciampi, Giovanni; Scorpio, Michelangelo; Spanodimitriou, Yorgos; Rosato, Antonio; Sibilio, Sergio
Abstract: This study discusses a full-scale Electric-Driven smart window from both an experimental and numerical point of view. The first part of this paper reports the experimental performances of the investigated smart window, using a full-scale outdoor test-room. The tests are carried out during the summer under real sky conditions varying the state of the Electric-Driven window (clear and milky). In the second part, a numerical model is developed and validated using the data acquired during the in-situ experiments. Finally, the developed simulation model is used to assess the performances of the Electric-Driven window varying the switching control strategies (from clear to milky and vice versa) in a refurbishment case study of a building office façade located in the south of Italy. In particular, the reduction of the indoor air temperature (up to 2.1 °C), the reduction of cooling energy demand (up to about 41.0%), the primary energy saving (up to about 4.0%) and the reduction of carbon dioxide equivalent emissions (up to about 2.2%) are evaluated. The analysis is performed comparing the simulation results associated to a case with the Electric-Driven window with those where a typical double glass low-e window is used. Highlights: A full-scale ED smart window based on LC/PDLC technology is tested in-situ. A simulative model of an ED smart window based on LC/PDLC technology is developed. The ED window model is used in the refurbishment of a typical office building. The cooling energy demand is reduced up to 41% when ED smart windows are used. The ED smart window reduces the indoor air temperature by up to 2.1 °C.